Pengaruh Kontribusi Kemandirian Belajar Terhadap Hasil Belajar Seni Tari Siswa Kelas X SMA Negeri 2 Padang - Husnul Khotimah; Fuji Astuti (SENDRATASIK UNP, 2022)
This study tries to find out what the contribution of students' independence in learning to dance is. This type of research is quantitative research, data is collected and processed using statistical formulas. The population of this quantitative research is class X SMA Negeri 2 Padang students who are registered for the 2020-2021 school year. Data were collected using a learning independence questionnaire and an (objective) test of dance learning outcomes. Before the data was analyzed, the data analysis requirements for normality and homogeneity were first tested. Further testing of the determinants was carried out to determine the contribution of independence in dance learning. The results showed that learning independence contributed 39.69% to the dance learning outcomes of class X 2 high school students and the rest (60.31%) was influenced by other factors. Based on the results of data analysis, it can be concluded that the independence of learning dance has a significant effect on the learning outcomes of dance.